Analysis of Risk Factors Affecting Incidents of Confirmed Pulmonary Tuberculosis in The Region North Sumatra in 2023 - Amirah, Asriwati; Suharto, Teguh; Suarayasa, Ketut; Muhamad, Zuriati; Nadapdap, Faskanita Maristella (Migration Letters, 2024)
TB is one of the deadliest infectious diseases in the world, namely an infectious disease caused by infection with the Mycobacterium tuberculosis bacteria in the lungs. Tuberculosis (TB) is a major global health problem with an estimated 10.4 million new TB cases worldwide. The aim of this research is to determine the relationship between risk factors and the confirmed incidence of pulmonary TB in North Sumatra in 2022. The research method uses case control with a purposive sampling technique, the sample size is rounded up to 750 cases, with a ratio of 1:1 so the number of controls is also 750 so the total sample a total of 1500 Cases. This data is then analyzed using Path Analysis to predict the incidence of pulmonary TB. The results of the research obtained using a logistic regression test showed that the factor most at risk for transmission of pulmonary TB was house density with a value of OR = 3.32. Meanwhile, based on Path Analysis, the factors associated with confirmed pulmonary TB were house density and physical environment, while disease history and Smoking was not associated with confirmed pulmonary TB (t<1.96). It is recommended to pay attention to lighting at home and environmental cleanliness to stop transmission of the virus through the air inhaled by susceptible individuals.